Gender and the Telephone: Voice and Emotions Shaping and Gendering Space - Livholts, Mona; Bryant, Lia (Human Technology, 2013)
In the field of communication studies, the topic of telephony and the gendering of space via voice and emotions has received limited attention. The focus of this article is how telephone conversations are mediated by voice and emotions, which in turn shape and gender social space. The methodology is a collaborative autoethnographic design based on diary notes and memory work. Two central themes emerge from the findings that explain how space becomes gendered when using the telephone: (a) the voice and relations of power, and (b) the interstices between work, caring, and the telephone. Our findings reveal the central role of work and caring and how these spaces constantly are being traversed and transformed as the mobile phone becomes an important appendage for sensory perceptions of hearing/listening/voice. We argue that these themes point toward the crucial impact of emotions in the construction of multiple and gendered spatialities of telephony.